(untitled) (Journal of Philosophy Culture and Political Science, 2019)
This article show that Sufi sm is considered to be spiritual culture in the Islamic world, that perform a diffi cult translator’s function of base traditions, of values, of philosophical orientation, which can be evolved with the help of dominant facts of Islamic culture, etc. Arabic and religion. From the one hand, Sufi sm adapts new values by transforming their external form, changing the meaning of previous patterns. From the other hand, performing the missionary, apologetically function, Sufi sm adapt the spiritual guidance of non Arabic people to the Islam, offering a solving some diffi cult philosophical problems in compromise form. At this moment, Sufi sm perform the function of preserving ethnic memory. This fact explains that Sufi sm get its distribution in Central Asia, where Islam takes a part in new reality – in the world of Islamic culture. Keywords: Sufi sm, spiritual culture, new values,суфизм, духовная культура, новые ценности, the philosophical landmarks, Islam culture.